Mantoniella beaufortii and Mantoniella baffinensis sp. nov. (Mamiellales, Mamiellophyceae), two new green algal species from the high arctic1. Issue 1 (17th November 2019) - Yau, Sheree; Lopes dos Santos, Adriana; Eikrem, Wenche; Gérikas Ribeiro, Catherine; Gourvil, Priscillia; Balzano, Sergio; Escande, Marie‐Line; Moreau, Hervé; Vaulot, Daniel
Abstract : Members of the class Mamiellophyceae comprise species that can dominate picophytoplankton diversity in polar waters. Yet, polar species are often morphologically indistinguishable from temperate species, although clearly separated by molecular features. Here we examine four Mamiellophyceae strains from the Canadian Arctic. The 18S rRNA and Internal Transcribed Spacer 2 (ITS2) gene phylogeny place these strains within the family Mamiellaceae (Mamiellales, Mamiellophyceae) in two separate clades of the genus Mantoniella . ITS2 synapomorphies support their placement as two new species, Mantoniella beaufortii and Mantoniella baffinensis . Both species have round green cells with diameter between 3 and 5 μm, one long flagellum and a short flagellum ( 1 μm) and are covered by spiderweb‐like scales, making both species similar to other Mantoniella species. Morphologically, M. beaufortii and M. baffinensis are most similar to the cosmopolitan M. squamata with only minor differences in scale structure distinguishing them. Screening of global marine metabarcoding data sets indicates M . beaufortii has only been recorded in seawater and sea ice samples from the Arctic, while no environmental barcode matches M. baffinensis . Like other Mamiellophyceae genera that have distinct polar and temperate species, the polar distribution of these new species suggests they are cold or ice‐adapted Mantoniella species.